2008
DOI: 10.1002/ppul.20828
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory symptoms and general illness during the first year of life: A population‐based birth cohort study

Abstract: Respiratory symptoms are common in infancy. Most illnesses occurring among children are dealt with by parents and do not require medical attention. Nevertheless, few studies have prospectively and on a community-basis assessed the amount of respiratory symptoms and general illness in normal infants. In this population-based birth cohort study, 228 healthy infants from Copenhagen, Denmark were followed from birth to 1 year of age during 2004-2006. Symptoms were registered using daily diaries and monthly home vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
64
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 24 publications
7
64
1
Order By: Relevance
“…First, the different types of pet animals have not been evaluated separately in the analyses. 5,16,20,21,28 Second, some studies enrolled older children. For example, Burr et al 16 found that pet ownership increased the risk of wheezing, rhinitis, and the number of cold episodes per year for 12-to 14-year-olds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the different types of pet animals have not been evaluated separately in the analyses. 5,16,20,21,28 Second, some studies enrolled older children. For example, Burr et al 16 found that pet ownership increased the risk of wheezing, rhinitis, and the number of cold episodes per year for 12-to 14-year-olds.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In previous reports, the frequency of respiratory tract infections has been estimated to vary between 3 and 6 episodes within the first year of life. [4][5][6] A variety of factors, such as day care attendance, 7,8 older siblings 7,9,10 and lack of breastfeeding, [10][11][12] have been considered as possible risk factors for early respiratory tract infections. In addition, a parental history of asthma 13,14 and smoking 10,[15][16][17][18] are thought to have a role in the child' s susceptibility to infections and to respiratory symptoms.…”
mentioning
confidence: 99%
“…Parents make a considerable use of healthcare services to cope with ARI, thus becoming a burden for children and their families (1,4). Furthermore, ARI are the main cause of worldwide morbidity, leading to school and work absenteeism (5).…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory infections are common in all pediatric age groups, including the youngest patients. For example, a population-based survey reported that healthy infants experienced acute respiratory symptoms for an average of 3.5 months during their fi rst year of life, with the average infant experiencing six episodes of acute respiratory illness and six episodes of simple rhinitis during that year [2]. Furthermore, the Asthma and Allergy Foundation of America reported that allergy is the third most common chronic disease in children [3], and children with allergies are predisposed to developing upper respiratory tract infections, rhinosinusitis, and OM [4].…”
Section: Introductionmentioning
confidence: 98%